2002
DOI: 10.1017/s0967026202003955
|View full text |Cite
|
Sign up to set email alerts
|

In situidentification and localization of bacteria associated withGyrodinium instriatum(Gymnodiniales, Dinophyceae) by electron and confocal microscopy

Abstract: The presence of intracellular bacteria in the dinoflagellate Gyrodinium instriatum Freudenthal & Lee has previously been described but the bacterial flora associated with this species has not been characterized. In this study, new results of transmission electron microscopy (TEM) and in situ hybridization using several bacterial group-specific oligonucleotide probes are presented. The long-term association of endocytoplasmic and endonuclear bacteria with G. instriatum has been confirmed. All endonuclear and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 46 publications
0
27
0
2
Order By: Relevance
“…The literature presents different views about the type of specificity of the association between bacteria and HABs. For example, while some authors have identified the Bacteroidetes as associated with Alexandrium dinoflagellates (Biegala et al 2002), other studies have convincingly shown that the Roseobacter subgroup of Alphaproteobacteria and the Alteromonas subgroup of Gammaproteobacteria are almost always associated with blooming Alexandrium (Brinkmeyer et al 2000, Sala et al 2005. Field studies relating HABs and the composition of the associated bacteria have focused primarily on successional changes and the possible inhibition or stimulation of blooms by the bacteria (Buck & Pierce 1989, Romalde et al 1990, Fukami et al 1991, Onji et al 1995, Ishida et al 1997 or their implication in the production and biotransformation of paralytic shellfish toxins (PSTs) (Tobe et al 2001).…”
Section: Abstract: Fish · Dinoflagellates · Hab · Alexandrium · Rosementioning
confidence: 99%
See 1 more Smart Citation
“…The literature presents different views about the type of specificity of the association between bacteria and HABs. For example, while some authors have identified the Bacteroidetes as associated with Alexandrium dinoflagellates (Biegala et al 2002), other studies have convincingly shown that the Roseobacter subgroup of Alphaproteobacteria and the Alteromonas subgroup of Gammaproteobacteria are almost always associated with blooming Alexandrium (Brinkmeyer et al 2000, Sala et al 2005. Field studies relating HABs and the composition of the associated bacteria have focused primarily on successional changes and the possible inhibition or stimulation of blooms by the bacteria (Buck & Pierce 1989, Romalde et al 1990, Fukami et al 1991, Onji et al 1995, Ishida et al 1997 or their implication in the production and biotransformation of paralytic shellfish toxins (PSTs) (Tobe et al 2001).…”
Section: Abstract: Fish · Dinoflagellates · Hab · Alexandrium · Rosementioning
confidence: 99%
“…Methods based on the detection of bacterial 16S rRNA genes with oligonucleotide probes represent a useful tool to gain insight into the composition of bacterioplankton assemblages (Glöck-ner et al 1999); these methods are independent of PCR biases. This approach has allowed the detection of highly specific bacterial assemblages on lake snow (Schweitzer et al 2001) and riverine aggregates (Böck-elmann et al 2000), has been used to study the specificity of associations in some HABs , and has also been proven useful for the identification, localisation and quantification of intracellular and associated bacteria in dinoflagellate cultures (Biegala et al 2002). For our purpose of determining the composition of the bacterial assemblage accompanying the HAB species, a quantitative, cell-based detection method such as fluorescent in situ hybridisation (FISH) seemed most appropriate.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, only members of the phylum Proteobacteria have been identified as intranuclear bacterial symbionts of protists and other eukaryotes (Alverca et al, 2002;Fokin, 2004;Arneodo et al, 2008;Zielinski et al, 2009). Based on their morphology, 'Candidatus Nucleococcus' (abbreviated hereafter as Nucleococcus) closely resembled Caryococcus nucleophagus, described by Kirby (1944) for the intranuclear symbionts of Trichonympha corbula, as 'Spherules with a diameter of 1/2 mm, sometimes arranged in pairs, sometimes with a thicker, crescentic, stainable area at the periphery on one side...' The genus Caryococcus was originally described for an intranuclear symbiont of the euglenid protist Euglena deses by Dangeard (1902).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that dinoflagellate-associated bacteria (DABs) may have a role as algal growth and bloom dynamics regulators, that they can be involved in dinoflagellate toxin production, and that some have algicidal properties (4,5,8,9,10,11,14,15,17,20,21,24,28,29). The relationship between dinoflagellates and DABs has generally been postulated to be symbiotic, as the two organisms coexist and, in some cases, the association is maintained for a long time (1,5,6,10,12,16).…”
mentioning
confidence: 99%